2016
DOI: 10.1101/gr.197046.115
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC-induced mutations in human cancers are strongly enriched on the lagging DNA strand during replication

Abstract: APOBEC3A and APOBEC3B, cytidine deaminases of the APOBEC family, are among the main factors causing mutations in human cancers. APOBEC deaminates cytosines in single-stranded DNA (ssDNA). A fraction of the APOBEC-induced mutations occur as clusters ("kataegis") in single-stranded DNA produced during repair of double-stranded breaks (DSBs). However, the properties of the remaining 87% of nonclustered APOBEC-induced mutations, the source and the genomic distribution of the ssDNA where they occur, are largely unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
204
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(220 citation statements)
references
References 43 publications
15
204
1
Order By: Relevance
“…30 Additionally, analysis of nearly 4000 whole-genome and wholeexome sequenced cancers by Seplyarskiy, et al indicated enrichment of APOBEC3 signature mutations on lagging strand templates. 32 Together with our findings, this growing body of data reveals the susceptibility of ssDNA exposed during replication to mutagenesis by APOBEC3 enzymes.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…30 Additionally, analysis of nearly 4000 whole-genome and wholeexome sequenced cancers by Seplyarskiy, et al indicated enrichment of APOBEC3 signature mutations on lagging strand templates. 32 Together with our findings, this growing body of data reveals the susceptibility of ssDNA exposed during replication to mutagenesis by APOBEC3 enzymes.…”
Section: Discussionmentioning
confidence: 83%
“…This has been demonstrated by ectopic expression of human APOBEC3 enzymes in model organisms as well as analysis of cancer genomes. [30][31][32][33] Although these studies suggest ssDNA at replication forks is vulnerable to deamination by APOBECs, this has not been established experimentally in mammalian cells.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations